الغفلة والنسيان :‏ ‏دراسة موضوعية في ضوء القرآن /‏ - Abdul Hafiz Muhamad Muklis (Kulliyyat Ma'arif al-Wahy wa al-'Ulum al-Insaniyah, International Islamic University Malaysia, 2009)
This study examines the concept of forgetfulness and unawareness from a Quranic perspective. It begins by defining the concepts, detailing and analyzing their elements and categories. The study proceeds to show the difference between forgetfulness and unawareness, and their most important characteristics and aspects as illustrated by the Quran. The study exposes the aspects of forgetfulness and unawareness then links them to our contemporary life, scrutinizing the main causes behind these two concepts. After that, the study addresses the major ways for treating forgetfulness and unawareness, which every Muslim should follow. In all this, the researcher has followed the deductive and analytical approaches to reach the desired conclusions. One conclusion of the study is that forgetfulness and unawareness are broad subjects that cannot be summarized or fully addressed in one study. This is because every sin is a result of unawareness, and every negligence is a result of forgetfulness. However, pointing to some elements of forgetfulness and unawareness might be sufficient, and it might also help preachers and reformers as they play the most vital role in transforming the Ummah from forgetfulness and unawareness to light and remembrance, through their preaching, guidance, advice, and writings.